Eksplorasi Peranan Komunikasi melalui Instant Messenger pada Performa Tim Kerja Mahasiswa di Universitas - Ivan Arrilya Eka Trexano; Diah Priharsari; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Group work is an important part of the learning process at universities, especially during a pandemic where all learning is done online. Student group work is very dependent on communication made by group members because there is no possibility to communicate directly. Team Communication is done using instant messengers, so it is important to know what role instant messengers play in the communication of a student work team. The purpose of this study is to explore what role communication via instant messenger plays in the performance of an student work team. This study uses a qualitative approach. Semi-structured interviews became the main tool in data collection. The data is analyzed using thematic content analysis which produces patterns that appear in the data. Based on the results of interviews, it was found that instant messengers have an important role in team performance where they act as a team connection tool, reminders of tasks, helping individuals in communicating, saving energy in establishing communication, and a coordination tool. As for the performance itself, communication through instant messengers has an effect on the score of team assignments and team member satisfaction, but has less effect on the completion of tasks according to the existing deadlines.